N1-Arylation of 1,4-Benzodiazepine-2-ones with Diaryliodonium Salts - Khan, Raysa; Felix, Robert; Kemmitt, Paul D.; Coles, Simon J.; Tizzard, Graham J.; Spencer, John (Synlett, 2018)
A library of N1-arylated 5-phenyl-1,3-dihydro-2H-1,4-benzodiazepin-2-ones has been synthesized starting with unsymmetrical diaryliodonium salts using aqueous ammonia as a base. This can also be applied to a similar 1,3,4-benzotriazepin-2-one derivative.
Keywords: benzodiazepines; N-arylation; iodonium salt; privileged scaffold; benzotriazepine